1976
DOI: 10.1021/ja00417a014
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal structure of ferrioxamine E

Abstract: The crystal structure of ferrioxamine E, Caa^sNsOgFe-l.S^O, has been determined with single-crystal x-ray diffraction. The crystals are triclinic, space group P\, two molecules per unit cell with dimensions a = 19.77 (1) A, b = 10.512 (2) k,c = 8.029 (2) A, a = 106.84 (2)°, ß = 93.91 (2)°, and y = 97.74 (3)°. The intensity data (3963) were collected on an automatic diffractometer. The structure, determined by the heavy-atom method, was refined by least-squares methods. The final R was 0.076 for all data. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
2
3

Year Published

1981
1981
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 6 publications
3
34
2
3
Order By: Relevance
“…This contrasts directly with the fac geometry found for the Ga analogue (14). As observed previously in structures of Ga3+ (14), SnJ+ (18-21), Fe3+ (22)(23)(24)(25)(26)(27), Cr3+ (28), and zn2+ (29) . Correction for differences in effective ionic radii (30) shows that the hydroxamate moiety makes a stronger chelate with In3+ than with sn3+, in which complexes the Sn-0 bonds are relatively much longer, especially Sn-O(C) (1 8-21).…”
Section: X-ray Crystallographic Analysis Of Tris(benzohydroxamato)indcontrasting
confidence: 80%
See 2 more Smart Citations
“…This contrasts directly with the fac geometry found for the Ga analogue (14). As observed previously in structures of Ga3+ (14), SnJ+ (18-21), Fe3+ (22)(23)(24)(25)(26)(27), Cr3+ (28), and zn2+ (29) . Correction for differences in effective ionic radii (30) shows that the hydroxamate moiety makes a stronger chelate with In3+ than with sn3+, in which complexes the Sn-0 bonds are relatively much longer, especially Sn-O(C) (1 8-21).…”
Section: X-ray Crystallographic Analysis Of Tris(benzohydroxamato)indcontrasting
confidence: 80%
“…G a ( b~)~ (14) and Cr(bz), (28) are the only structurally characterized metal hydroxamates to have the difference between M -O ( C ) and M-0(N] as small as it is in the present structure (0.014, 0.022, 0.039 A); in the Cr complex, this was ascribed to a crystal-field effect (28) that is not available to Ga or I n ( b~)~. The u p a l difference between M -4 ( C ) and M -O ( N ) is 0.05-0.1 1 A (14,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)29). Because all possible hydrogen bond donors in the In(bz), structure are so utilized (e.g., the N-H), there is likely an addition of electron density to the N -0 , causing this bond to be anomalously short relative to other values.…”
Section: X-ray Crystallographic Analysis Of Tris(benzohydroxamato)indcontrasting
confidence: 53%
See 1 more Smart Citation
“…Despite the wide interest, the structural results of ferrioxamines are limited. The only reported crystal structures are those of ferrioxamine E (van der Helm & Poling, 1976) and deferriferrioxamine E (Hossain, van der Helm & Poling, 1983). Because of its kinetic lability, the structural features of ferrioxamine B could not be characterized from solution studies, but it has been shown that the more stable Cr 3+ complex of deferriferrioxamine B (and also of D ~) exists as a mixture of two geometrical isomers, with eis and trans configuration (Leong & Raymond, 1975).…”
Section: -2701/86/101305-0650150mentioning
confidence: 99%
“…The absorption corrections were calculated with the program of Coppens, Leiserowitz & Rabinovich (1965), employing a Gaussian method and a 6 x 6 x 6 grid. Each structure factor was assigned a weight (van der Helm & Poling, 1976).…”
Section: Introductionmentioning
confidence: 99%